Trends in the Development of Extremism Among Youth in Modern Russian Society: Internal and External Challenges to National Security - Vladimirovich Serikov, Anton; Sergeevna Panfilova, Yulia (International Journal of Engineering and Technology, 2018)
Neutralization of the risks of extremism among youth and the integration of at-risk groups of young people in various spheres of public life – a problem that is of particular importance for Russian national security. The successful solution of the problem, while the "fluid" social reality is changing, is only possible if we take into account the recent trends in the development of extremist formations with due regard for network communities, flash mobilization groups. The article is dedicated to the analysis of the trends of youth extremism reconfiguration that occur in modern Russian society, and the contradictions of reactive counteraction policy, the principles of which are not always integrated in a new social reality. The authors substantiate the application of the potential of the activity-activist approach, including the tendency to the definition of youth extremism as a volatile social phenomenon with a highly adaptive potential. Based on the results of the research, the authors describe the new internal and external development challenges of extremist groups in Russia: the creation of new topics for manipulating mass consciousness (socio-ecological, social identity-related , culturally-oriented); "dispersion" of extremist structures; inclusion in legal social actions; positioning as open to young people without "preconditions"; inclusion of conventional relations within the framework of the exchange of ideas and "projects". In conclusion, the authors note that recognition of the internal and external challenges of youth extremism requires reformatting its perception and evaluation as a new movement which produces new risks for Russian society.